Interferensi Bahasa Sasak Ke Bahasa Inggris pada Santriwati Ponpes Nashriyah NW Sekunyit - Selamet Riadi; Hafifatul Fajriah (P@RAD!GMA : Jurnal Kajian Budaya & Media, 2023)
This study aims to identify and describe forms of interference from the Sasak language into English by female students at the Nashriyah NW Sekunyit Islamic Boarding School. This qualitative descriptive research using an embedded case study strategy used the female students of the Nashriyah NW Sekunyit Islamic Boarding School as a data source. The data collection methods used are the Proficient Involved Listening (SLC) and Proficiency Involved Free Watch (SBLC) methods with the assistance of recording techniques so that collection is easier to do. The data that has been collected is then transcribed, classified, and analyzed. To maintain the validity of the data, the data was analyzed both during the data collection process or pre-analysis and after data collection was completed or post-analysis. The results of the data analysis proved that there was interference from the Sasak language into English by female students at the Nashriyah NW Sekunyit Islamic Boarding School. There are three forms of interference, namely sentence syntax interference, morphological interference, and phonological interference. Of the three interferences, it is morphological interference that is most often carried out by female students at the Islamic Boarding School Nashriyah NW Sekunyit. The reason they interfere is because of the influence of their mother tongue on the English they are learning, as well as their lack of mastery of English.